Cost saving via graph coloring approach - Fecková Škrabuľáková, Erika; Grešová, Elena (Univerzita Pardubice, 2019)
The implementation of graph algorithms on diverse tasks of economic problems has reducing costs potential in different areas of business activities. In the present paper we deal with an identification of optimal allocation of guide signs in a large exhibition hall with given spatial organization, when the move of a visitor is allowed only along given corridors. In order to achieve our aim we use modeling by a graph and graph coloring algorithm approach. Although our implementation model concerns distribution of issues in a large exhibition hall, similar algorithm could be utilized in many other navigational situations. Solving these kinds of tasks is relevant from economic point of view, because it reflects in cost saving and business prosperity. The better is the organization of the event, the greater is the satisfaction of clients and exhibitors, the higher is the probability that they will come again and that the business will prosper for each of the parties involved.
Keywords: cost saving; modeling via graphs; optimal distribution of issues; palette coloring; C61; C65